Sauchinone Inhibits the Proliferation and Immune Invasion Capacity of Colorectal Cancer Cells through the Suppression of PD-L1 and MMP2/MM9 - Lu, Yiping; Yu, Miao; Ye, Jinsheng; Liang, Yankai; Gao, Jianxin; Ji, Zhen; Wang, Jie (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Colorectal cancer (CRC) is one of the most common tumors globally and a leading cause of cancer-related death. In China, CRC is the third most common cancer type. Sauchinone is known to exhibit anti-tumor and anti-inflammatory activity, but its effects on CRC have not been investigated to-date Objective: To investigate the effects of Sauchinone on CRC development and metastasis and its underlying mechanism( s) of action. Methods: SW480 and HCT116 cells were treated with a range of concentrations of Sauchinone. Cell proliferation was measured using EDU assays and flow cytometry. Results: Treatment with 50 μM Sauchinone decreased the expression of MMP2 and MMP9 and downregulated PD-L1 expression (PD-1/PD-L1) leading to checkpoint inhibition. Sauchinone treatment also enhanced the cytotoxicity of SW840 and HCT116 cells co-cultured with CD8+ T cells. The overexpression of PD-L1 rescued the anti-proliferative and cytotoxic effects of Sauchinone in both types. Conclusions: We show that Sauchinone suppresses CRC cell growth through the downregulation of MMP2 and MM9 expression and PD-1/PD-L1 mediated checkpoint inhibition. Collectively, these data highlight the promise of Sauchinone as a future anti-CRC therapeutic.
Keywords: Colorectal cancer